The association between traumatic experiences and anxiety among adoptees with autism spectrum disorder. - Kim, Irang; Lee, Jaegoo; Mowbray, Orion; Brodzinsky, David (International Journal of Developmental Disabilities, 2026)
The influence of traumatic experiences (TEs) on occurrence of anxiety among adoptees with autism spectrum disorders (ASD) is poorly understood. Adoptees with ASD who have TEs are at risk for psychiatric disorders. The purpose of this study was to determine whether TEs significantly influence the diagnosis of anxiety. Using data from the Modern Adoptive Families Study, this study includes 60 of the 1,616 adoptive parents whose first adoptee was diagnosed with ASD ages 2 to 28 years. Multivariate modeling demonstrated that experiences of neglect before adoption was associated with a parent-reported diagnosis of anxiety (OR = 5.01, p < 0.05). In addition, cumulative TEs before adoption were associated with a parent-reported diagnosis of anxiety (OR = 1.67, p < 0.05). Results underscore the importance for professionals to screen for various indicators of TEs when evaluating and treating anxiety among adoptees with ASD.